The impact of the teacher education study program on the development of TPACK - Dobi Barišić, Karolina; Brust Nemet, Maja (Revija za elementarno izobraževanje, 2023)
The results showed statistically significant difference for Technological, Pedagogical and Content Knowledge, for all students in the sample and for students with additional computer science courses. In the case of overall TPACK, there is no difference for overall sample of students but for students with additional computer science courses difference is significant.
Keywords: pedagogical knowledge, pre-service teachers, teacher education, technological knowledge, TPACK